Promoting Surgical Residents' Basic Skills via the Design and Implementation of a Simulation Training Tool. (August 2019) - Ruoranen, Minna; Antikainen, Teuvo; Mattila, Anne; Hämäläinen, Raija H.; Eteläpelto, Anneli
Background. Surgical training in authentic work environments needsguidance practices, including simulation training within acompetence-based framework . The use of simulators may actually have negative effects on professional learning if there is a lack of competence-based goals, tools, and guidance, integrated with work practices, and applied by trainers. Intervention. We designed simulation training tools to promote the surgical residents' abilities to perform competently in basic surgical skills. Our educational and surgical team worked together and (i) specified the goals for the tasks, (ii) specified the skills to be achieved, (iii) and analyzed the learning outcomes. The assumption was that after completing the simulation training, the resident would gain precise basic skills. Methods. Eight (8) licensed doctors, starting their specialization in surgery or gynecology, participated in the study. In accordance with the training design the residents were asked toself-assess their achieved skills by completing questionnaires, before and after the training period. In addition, the skills achieved were assessed individually by the trainer at the end of the training period. All the assessments were carried out on a scale based on OSATS (Objective Structured Assessment of Technical Skills) and modified specifically for this study. Results. The residents and their trainers evaluated the simulation training design as effective, and as beneficial for learning basic surgical skills. However, it proved difficult for the residents to achieve the targets consistently and to assess their own skills. Some fine-tuning is needed to enhance the integration of simulation training tools with practical learning. Discussion. The simulation training appeared to motivate the trainees. Overall, there is a need for discussion on the implications for competence-based theories and simulation practices. Limitations. The small number of participants limited the possibilities for statistical analysis. The analyses and results should be seen as merely indicative. Further studies are needed.